Internet pornography viewing preference as a risk factor for adolescent Internet addiction: The moderating role of classroom personality factors - Alexandraki, Kyriaki (J Behav Addict, 2018)
BACKGROUND AND AIMS: Adolescent Internet pornography viewing has been significantly increased in the last decade with research highlighting its association with Internet addiction (IA). However, there is little longitudinal data on this topic, particularly in relation to peer context effects. This study aimed to examine age- and context-related variations in the Internet pornography–IA association. METHODS: A total of 648 adolescents, from 34 classrooms, were assessed at 16 years and then at 18 years to examine the effect of Internet pornography preference on IA in relation to the classroom context. IA was assessed using the Internet Addiction Test (Young, 1998), Internet pornography preference (over other Internet applications) was assessed with a binary (yes/no) question, and classroom introversion and openness to experience (OTE) with the synonymous subscales within the Five Factor Questionnaire (Asendorpf & Van Aken, 2003). RESULTS: Three-level hierarchical linear models were calculated. Findings showed that viewing Internet pornography exacerbates the risk of IA over time, while classroom factors, such as the average level of OTE and introversion, differentially moderate this relationship. DISCUSSION AND CONCLUSION: The study demonstrated that the contribution of Internet pornography preference (as an IA risk factor) might be increased in more extroverted classrooms and decreased in OTE classrooms.